Incidence Trends of Five Common Sexually Transmitted Infections Excluding HIV From 1990 to 2019 at the Global, Regional, and National Levels: Results From the Global Burden of Disease Study 2019 - Fu, Leiwen; Sun, Yinghui; Han, Min; Wang, Bingyi; Xiao, Fei; Zhou, Yiguo; Gao, Yanxiao; Fitzpatrick, Thomas; Yuan, Tanwei; Li, Peiyang; Zhan, Yuewei; Lu, Yong; et al. (Frontiers in Medicine, 2022)
Objective: Sexually transmitted infections (STIs) are common worldwide and pose a challenge to public health. We conducted this study to assess the annual incidence of five common STIs including syphilis, chlamydia, gonorrhoea, trichomoniasis, and genital herpes at the global, regional, and national levels. Materials and Methods: We obtained detailed data on STIs excluding HIV from 1990 to 2019 from the Global Burden of Disease (GBD) 2019 database. Estimated annual percentage change (EAPC) was calculated to quantify trends in age-standardized incidence rates (ASR) of STIs, stratified by gender, sociodemographic index (SDI) region, and pathogenic microorganism. Results: Globally, incident cases of STIs increased by 58·15% from 486·77 million in 1990 to 769·85 million in 2019, but annual change in ASR was only −0·04% (95% CI −0·09 to 0·01) per year. EAPC was 0·16 (0·06 to 0·26) for syphilis, 0·09 (0·05 to 0·13) for genital herpes, 0·06 (0·03 to 0·09) for trichomoniasis, −0·21 (−0·36 to −0·06) for chlamydia, and −0·14 (−0·19 to −0·08) for gonorrhoea. High SDI regions reported significant increases in ASR of syphilis and chlamydia. Conclusions: The burden of disease from STIs remains large, though control of STIs has contributed to the decreasing incidence in most regions, especially in low-SDI region. Globally, over the past 20 years the ASR has remained stable for trichomoniasis and genital herpes, decreased for chlamydia and gonorrhoea, and increased for syphilis.